IMPLEMENTASI PASAL 470 PERATURAN GUBERNUR LAMPUNG NOMOR 56 TAHUN 2019 TERHADAP PEMANTAUAN BIDANG PENGELOLAAN DAN LAYANAN INFORMASI PUBLIK DI LINGKUP PEMERINTAH PROVINSI DALAM MENDUKUNG KEBIJAKAN NASIONAL DAN PEMERINTAH PROVINSI (Studi di Dinas Komunikas - Dian Herlambang; Prastio Budi Wibowo (Universitas Bandar Lampung (UBL), 2021)
The Lampung Governor's Regulation Number 56 of 2019 was issued as an effort to determine the position, organizational structure, duties and functions as well as the work procedures of the Lampung Province Communication, Information and StatisticsOffice. Policy implementation is required, referring to the views of experts that everypolicy that has been made must be implemented. How is the implementation of Article470 of Lampung Governor Regulation Number 56 of 2019 on monitoring the field ofmanagement and public information services within the scope of the provincialgovernment in supporting national and provincial government policies? What are thefactors that hinder the implementation of Article 470 of Lampung Governor RegulationNumber 56 of 2019 on monitoring the field of management and public informationservices within the scope of the provincial government in supporting national andprovincial government policies? The research method used in this paper is normativejuridical, and empirical approach. The data used are secondary data and primary data.Data analysis used qualitative juridical analysis. Research Results: Article 470 ofLampung Governor Regulation Number 56 Year has been implemented but there arestill some obstacles by the Field of Management and Public Information Services of theInformation Communications and Statistics Office of Lampung Province in carrying out their duties. Factors that hinder the implementation of Article 470 of Lampung Governor Regulation Number 56 of 2019 are caused by internal factors and externalfactors.Suggestions It is hoped that there will be a common view of all stakeholders andall levels of society in which direction the communication and information technologysector will be developed and the extent to which every level of society must activelyparticipate in achieving these common goals, as well as how progress and success rateswill be measured in the future.